Memantine: a review of studies into its safety and efficacy in treating Alzheimer’s disease and other dementias - Stuart J Thomas (Dove Medical Press, 2009)
Stuart J Thomas, George T GrossbergDepartment of Neurology and Psychiatry, Saint Louis University School of Medicine, St. Louis, MO, USAAbstract: Memantine is an uncompetitive N-methyl-D-aspartate receptor antagonist with moderate affinity. Its mechanism of action is neuroprotective and potentially therapeutic in several neuropsychiatric diseases. It has been approved by the FDA for the treatment of moderate to severe Alzheimer’s disease (AD) either as a monotherapy or in combination with cholinesterase inhibitors. This review covers key studies of memantine’s safety and efficacy in treating moderate to severe AD. It also covers current research into other dementias including but not exclusively mild AD and vascular dementia. Other studies on the efficacy of memantine for other neuropsychiatric diseases are discussed. Memantine is a safe and effective drug that merits further research on several topics. Clinicians should be aware of new studies and potential uses of memantine because of its safety and efficacy.Keywords: memantine, Alzheimer’s disease, dementia